Estimating direct genetic and maternal effects affecting rabbit growth and feed efficiency with a factorial design. (28th January 2019) - Garreau, Hervé; Ruesche, Julien; Gilbert, Hélène; Balmisse, Elodie; Benitez, Florence; Richard, François; David, Ingrid; Drouilhet, Laurence; Zemb, Olivier
Abstract: The aim of this experiment was to evaluate the significance of neonatal environment on feed efficiency. For that purpose, rabbits from a line selected for residual feed intake (RFI) during 10 generations (G10 kits) were cross‐fostered with non‐selected control does (i.e., G0 line), and reciprocally. In parallel, sibs were fostered by mothers from their original line. Nine hundred animals were raised in individual ( N  = 456) or collective ( N  = 320) cages. Traits analysed in this study were body weight at 32 days and at 63 days, average daily gain (ADG), feed intake between weaning and 63 days (FI), feed conversion ratio (FCR) and RFI. The maternal environment offered by does from the line selected for RFI deteriorated the FCR of the kits, independently of their line of origin, during fattening (+0.08 ± 0.02) compared to FCR of kits nursed by G0 does. The line, the type of housing and the batch were significant effects for all the measured traits: G10 kits were lighter than their G0 counterparts at 32 days (−82.9 ± 9 g, p  < 0.0001) and at 63 days (−161 ± 16 g, p  < 0.0001). They also had a lower ADG (−2.36 ± 0.36 g/day, p  < 0.0001), RFI (−521 ± 24 g/day, p  < 0.0001) and a lower FI (−855 ± 31 g, p  < 0.0001), resulting in a more desirable feed efficiency (FCR: −0.35 ± 0.02). There was no significant difference in the contrast of G10 and G0 performances between collective and individual/digestive cages ( p  > 0.22): −2.35 g/day versus 2.94 g/day for ADG, −0.39 versus −0.40 for FCR, −577 g versus −565 g for RFI and −879 g versus −859 g for FI, respectively). Thus, no genotype‐by‐environment (housing) interaction is expected at the commercial level, that is, no re‐ranking of the animals due to collective housing.